Editorial: On Making the Work of Women Editors Visible - Heftberger, Adelheid; Grgic, Ana (Apparatus. Film, Media and Digital Cultures of Central and Eastern Europe, 2019)
<span id="docs-internal-guid-0d22a75e-7fff-7dcd-b88f-7b605cad9c1e" style="font-size: 12pt; font-family: ’Times New Roman’; color: #000000; background-color: transparent; font-weight: 400; font-style: normal; font-variant: normal; text-decoration: none; vertical-align: baseline; white-space: pre-wrap;"> <span style="font-size: 12pt; font-family: ’Times New Roman’; color: #000000; background-color: transparent; font-weight: 400; font-style: normal; font-variant: normal; text-decoration: none; vertical-align: baseline; white-space: pre-wrap;">The editorial article to the themed issue 7 Women Cutting Movies: Editors from East and Central Europe. <span style="font-size: 12pt; font-family: ’Times New Roman’; color: #000000; background-color: transparent; font-weight: 400; font-style: normal; font-variant: normal; text-decoration: none; vertical-align: baseline; white-space: pre-wrap;">Cover image from Jane Austen’s Manuscript The Watsons (https://janeausten.ac.uk), cited in the article of Szilvia Ruszev Rhythmic Trajectories - Visualizing Cinematic Rhythm in Film Sequences.